An Insight into the Economics that Underpin the Dynamic Allocation of Road Space Using Traffic Signals in New South Wales1. Issue 2 (19th April 2016) - Chong‐White, Christian
Abstract : This paper provides insight into the economics that underpin the dynamic, real‐time allocation of scarce road space using traffic control in New South Wales (NSW). We explain the history and status of the underlying system, SCATS, that was first created and is continually developed in NSW, and which has also been adopted across the other Australian states, and internationally. Using the results of traffic microsimulation modelling and analysis we provide evidence of the social benefit delivered to NSW by traffic control operation. This paper's contribution is the novel presentation of these facts and perspectives to the Australian economic community.